‘Ask a Geologist’ at Market Hall Museum, Warwick - Kathrin Schütrumpf; Gareth Jenkins; Julie Harrald (Geoconservation Research)
‘Ask a Geologist’ is a regular Saturday morning event at a local museum where the general public meets geologists, learning about geology and the identification of rocks, fossils and minerals. The events are a collaboration between the county geoconservation group (Warwickshire Geological Conservation Group) and the local museum (Warwick Market Hall Museum). ‘Ask a Geologist’ is attracting many visitors and raising public awareness and appreciation for Earth science and Earth heritage.